Evaluation of Online Learning Platforms in Latin America - Carlos Ramos-Galarza; Omar Cóndor-Herrera; Jorge Cruz-Cárdenas (Emerging Science Journal, 2022)
Introduction: The use of online learning platforms has made a huge contribution to the online learning process. A key tool in this world is videoconferencing, which allows the efficient advancement of knowledge of a specific subject during synchronized timing. Objective: With this proposed context, the objective of this investigation is to determine which online video-conference platform has more benefits to be applied in Latin America. Method: A study was carried out with a quantitative method, transversal temporality, and a correlational and comparative process. There was a sample of 272 participants between 12 and 55 years old. Results and conclusion: It was found that the platform with the most benefits according to the analysis of gender, age, and profession is ZOOM. These results allow us to analyze the usefulness of this platform and its benefits in the learning process in Latin America. Doi: 10.28991/ESJ-2022-SIED-018 Full Text: PDF